Regulatory cascade controls virulence in Vibrio cholerae. - DiRita, V J (1991)
Expression of more than 17 virulence genes in Vibrio cholerae is under the coordinate control of the ToxR protein. ToxR is a transmembrane protein that binds to and activates the promoter of the operon encoding cholera toxin. As yet, the ability of ToxR to activate directly other genes in this regulon has not been demonstrated. We have cloned a gene called toxT from V. cholerae 569B; the toxT gene product, like ToxR, can activate the ctx promoter in Escherichia coli. In addition, expression of other genes identified as members of the ToxR regulon (tcpA, tcpI, aldA, and tagA) can be activated in E. coli by the toxT gene product but not by ToxR. When expressed from a constitutive promoter, the toxT gene product partially suppresses the ToxR- phenotype of a toxR deletion mutant of V. cholerae. The level of toxT mRNA is greatly reduced in a toxR mutant of V. cholerae. In addition, growth conditions under which the ToxR regulon is not expressed also repress the synthesis of toxT mRNA. These results suggest that ToxR controls transcription of toxT, whose product in turn is directly responsible for activation of several virulence genes under ToxR control.